Mixed fermentation improved apple juice quality: juice characteristics and mechanism - Lei, Keyu; Wang, Yinglong; Pu, Yunfeng; Wang, Liling; Huang, Ying; Hou, Xujie (Frontiers in Nutrition, 2026)
IntroductionFermented apple juice demonstrates significant potential as a functional beverage with health-promoting benefits; however, optimizing its sensory quality remains challenging. This study investigated the effects of fermentation using single and mixed lactic acid bacteria (LAB) strains on the quality of ‘Red Fuji’ apple juice (AJ) from Aksu, Xinjiang.MethodsFlavor characteristics were assessed using electronic nose, electronic tongue, and HS-SPME/GC–MS, and underlying mechanisms were investigated via non-targeted metabolomics.ResultsThe results revealed that ‘Red Fuji’ AJ is an excellent fermentation substrate, with post-fermentation total colony counts consistently exceeding 8.5 log CFU/mL. Mixed fermentation outperformed single fermentation. At the L. helveticus and L. plantarum ratio of 1:2, yielding higher viable cell counts (>9.26 log CFU/mL), superior overall sensory acceptance (p < 0.05), and a more complex and pleasant flavor profile characterized by increased levels of esters, aldehydes, and alcohols, along with significantly reduced bitterness (65.3%) and astringency (74.1%). Metabolomic analysis identified key differential metabolites and metabolic pathways (amino acid metabolism, tricarboxylic acid cycle, and flavonoid biosynthesis), providing a theoretical basis for the flavor enhancement mechanism.DiscussionThis study demonstrates that specific mixed LAB fermentation can effectively address common sensory acceptance issues in fermented fruit juices by simultaneously enhancing probioticviability, enriching flavor complexity, and reducing undesirable tastes.